Composite water reducing agent for lithium slag concrete as well as preparation method and application of composite water reducing agent
By using composite water reducers, including siloxane modified polycarboxylic acid polymer and POSS-based silane coupling agent, the problem of water reducers adsorption in lithium slag concrete is solved, and the flexibility and durability are improved.
Patent Information
- Application Number
- CN202411982403.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Lithium slag is prone to adsorbing large molecular weight water reducing agents in concrete, resulting in a smaller slump in concrete, a decrease in fluidity, and a worse ease. Increasing the water-gluing ratio may cause water secretion and affect durability.
Complex water reducing agents are used, including siloxane modified polycarboxylic acid polymer solution, POSS-based silane coupling agent, polyethylene glycol and alkali exciter. The POSS-based silane coupling agent covers the pore structure of the lithium slag surface to prevent the adsorption of water reducing agents. The siloxane modified polycarboxylic acid polymer ensures the water reducing effect, and the alkali exciter compensates for the activity decreases.
Significantly improve the efficiency of lithium slag concrete, give full play to the water-reducing effect of water-reducing agent, and improve the flowability and durability of concrete.
Smart Images

Figure BDA0005221830480000061 
Figure BDA0005221830480000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polycarboxylic acid water reducers, and specifically relates to a composite water reducer for lithium slag concrete, a preparation method and application thereof. Background Art
[0002] Lithium slag (lithium carbonate slag) is industrial waste slag produced in the process of producing lithium carbonate by sulfuric acid method. Lithium slag has a yellowish-brown appearance, a large internal surface area and a porous structure. It is mostly glassy and not hydraulic. The chemical composition of lithium slag is similar to that of clay, mainly SiO2, Al2O3, Fe2O3, etc. Most of the SiO2 and Al2O3 in lithium slag exist in amorphous form and have high volcanic ash activity. Therefore, lithium slag can be used as an admixture in concrete. Lithium slag is used as an admixture in the preparation of concrete, which can not only absorb industrial solid waste lithium slag, but also reduce energy consumption and pollution emissions in the cement production process. It is an important way to save energy and reduce emissions, achieve green and low-carbon development, and has become a hot spot in the research and development of concrete. For example, patent CN110981322B discloses a nickel-iron slag aggregate concrete, which is prepared by mixing the following raw materials in parts by mass: 100-150 parts of cement, 100-200 parts of lithium slag powder, 1500-1800 parts of nickel-iron slag aggregate, 100-300 parts of nickel-iron slag powder, 5-20 parts of water reducer, 30-50 parts of polymer emulsion, and 120-150 parts of mixing water. Patent CN106316248B discloses a low shrinkage and high-strength concrete prepared using waste slurry from a concrete mixing station. The concrete concrete is composed, by weight, of 300-340 parts of cement, 90-130 parts of lithium slag, 70-110 parts of waste slurry from a concrete mixing station, 696-739 parts of river sand, 1044-1109 parts of crushed stone, 8.5-10 parts of shrinkage reducer, 4-6 parts of water reducer and 80-92 parts of water.
[0003] The above are all applications of lithium slag as an admixture to replace cement in the preparation of concrete, which can give full play to the volcanic ash activity of lithium slag and reduce the amount of cement to a certain extent, so as to achieve efficient utilization of resources and effective control of costs. However, lithium slag itself has a large internal surface area and a porous structure, which can easily absorb commonly used large molecular weight water reducers, especially comb-type polycarboxylic acid water reducers, reduce the effective water reducer content in concrete, reduce the slump of concrete, reduce fluidity, and lead to poor workability. In this scenario, in order to reduce the difficulty of construction, the water-cement ratio has to be increased, and the increase in the water-cement ratio may cause water seepage, which has an adverse effect on the durability of concrete.
[0004] Therefore, it is necessary to develop a lithium slag concrete water reducer to improve the workability and durability of concrete using lithium slag as an admixture. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a composite water reducing agent for lithium slag concrete, a preparation method and an application thereof. The composite water reducing agent comprises a siloxane-modified polycarboxylic acid polymer solution, a POSS-based silane coupling agent, polyethylene glycol and an alkali activator, wherein the POSS-based silane coupling agent is a sacrificial agent and can preferentially cover / fill the pore structure on the surface of lithium slag under the action of polyethylene glycol, thereby hindering the lithium slag from adsorbing the siloxane-modified polycarboxylic acid polymer molecules; the siloxane-modified polycarboxylic acid polymer can ensure that it can not only adsorb and wrap other gelling particles in concrete, but also can be easily adsorbed on the lithium slag particles to play the role of a water reducing agent; the alkali activator has the effect of compensating for the decreased activity of the lithium slag caused by the coverage of the POSS-based silane coupling agent; under the synergistic and balanced action of the above components, the workability of the lithium slag concrete can be significantly improved, and the water reducing effect of the water reducing agent can be fully exerted.
[0006] To achieve the above object, the present invention adopts the following scheme:
[0007] A composite water reducing agent for lithium slag concrete comprises the following raw materials in parts by weight: 40-60 parts of siloxane-modified polycarboxylic acid polymer solution, 25-40 parts of POSS-based silane coupling agent, 3-5 parts of polyethylene glycol, and 20-25 parts of alkali activator, wherein the POSS-based silane coupling agent is prepared by Michael addition reaction of acryloxysilane and aminopropylheptyl-cage polysilsesquioxane in a molar ratio of 1:1-1.03; the siloxane-modified polycarboxylic acid polymer solution is prepared by polymerizing monoalkenyl polyether monomer, acrylic monomer, monoalkenyl dibasic acid, and unsaturated siloxane in a solution in a molar ratio of 1:2-3:2-3:0.1-0.3, and the solid content of the polycarboxylic acid polymer solution is 40-50wt%.
[0008] The acryloxysilane is selected from one or a combination of two or more of (3-acryloxypropyl)trimethoxysilane, 3-acryloxypropylmethyldimethoxysilane, (methacryloxymethyl)triethoxysilane, (methacryloxymethyl)methyldiethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, methacryloxypropylmethyldiethoxysilane, acryloxypropyltrimethoxysilane, methacryloxymethyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-trimethoxysilanepropyl acrylate, and 3-(triethoxysilyl)propyl methacrylate.
[0009] The POSS-based silane coupling agent is prepared by a method comprising the steps of:
[0010] Under an inert atmosphere, acryloxysilane and aminopropylheptyl-cage polysilsesquioxane are added to an organic solvent, a catalyst is added, and the temperature is controlled to react. After the reaction is completed, reduced pressure distillation is performed to obtain a POSS-based silane coupling agent.
[0011] The organic solvent is selected from one or a combination of two or more of benzene, toluene, acetone, tetrahydrofuran, and chloroform. The temperature control is to control the temperature at 30-60°C, and the reaction time is 3-8h. The catalyst is selected from one or a combination of two or more of triethylamine, tetramethylbutylene diamine, N,N-dimethylcyclohexylamine, N,N-dimethylbenzylamine, and N-ethylmorpholine. The amount of the catalyst is 1-2% of the total molar amount of acryloxysilane and aminopropylheptyl-cage polysilsesquioxane.
[0012] The monoalkenyl polyether monomer has a weight average molecular weight of 2400-3000 and is selected from one or a combination of allyl polyoxyethylene ether and allyl polyoxypropylene ether; the unsaturated acid monomer is selected from one or a combination of acrylic acid and methacrylic acid; the monoalkenyl dibasic acid is selected from one or a combination of itaconic acid, maleic acid, fumaric acid, and citraconic acid; the unsaturated siloxane is selected from one or a combination of two or more of allyl trimethoxy silane, allyl triethoxy silane, 3-butene triethoxy silane, vinyl trimethyl silane, vinyl triethoxy silane, vinyl dimethoxy silane, and vinyl methyl dimethyloxy silane.
[0013] The siloxane-modified polycarboxylic acid polymer solution is prepared by a method comprising the following steps:
[0014] Under an inert atmosphere, monoolefin polyether monomer, acrylic monomer, monoolefin dibasic acid, unsaturated siloxane and molecular weight regulator are added to water and mixed evenly, the temperature is increased, an initiator solution is added dropwise, and then the reaction is carried out at a constant temperature. After the reaction is completed, the pH and solid content are adjusted to obtain a siloxane-modified polycarboxylic acid polymer solution.
[0015] The molecular weight regulator is selected from one or a combination of two or more of thioglycolic acid, mercaptopropionic acid, mercaptoethanol, and isopropanol. The amount of the molecular weight regulator is 0.8-1.5wt% of the total amount of the polymerized monomer. The temperature is raised to 80-100°C, and the constant temperature reaction time is 3-8h. The concentration of the initiator solution is 5-10wt%, and the solvent is water. The initiator is selected from one or a combination of two or more of ammonium persulfate, potassium persulfate, and sodium persulfate, and the amount of the initiator is 1-3wt% of the total amount of the polymerized monomer. The initiator solution is dripped in 0.5-1h. The pH is adjusted to 7-9 with an alkali solution with a concentration of 30-40wt%, and the alkali solution is selected from one or a combination of two of sodium hydroxide solution and potassium hydroxide solution. The solid content is adjusted to 40-50wt% by adding water or distillation.
[0016] The number average molecular weight of the polyethylene glycol is 600-1000.
[0017] The activator is selected from one or a combination of two or more of sodium hydroxide, sodium sulfate, gypsum, sodium carbonate and sodium silicate.
[0018] The present invention also provides a method for preparing the composite water reducer for lithium slag concrete, comprising the following steps: taking a siloxane-modified polycarboxylic acid polymer solution, a POSS-based silane coupling agent, polyethylene glycol, and an alkali activator and mixing them evenly to obtain the composite water reducer for lithium slag concrete.
[0019] The present invention also provides a lithium slag concrete, comprising the following raw materials in parts by weight: 200-250 parts of cement, 50-80 parts of lithium slag, 20-40 parts of fly ash, 1-2 parts of early strength agent, 650-800 parts of sand, 850-1000 parts of crushed stone, and 8-10 parts of the above-mentioned composite water reducing agent.
[0020] The lithium slag concrete also includes water, and the mass ratio of the total mass of cement, lithium slag and fly ash to water is 1:0.3-0.35.
[0021] The present invention also provides a method for preparing the lithium slag concrete, comprising the following steps:
[0022] Mix the composite water reducing agent and water evenly, add lithium slag and mix evenly, add cement, fly ash, early strength agent, sand and crushed stone and mix evenly to obtain lithium slag concrete.
[0023] The lithium slag has a median particle size of 15-20 μm and a specific surface area of 500-800 m 2 / kg, of which the mass percentage is 5-9% CaO, 56-64% SiO2, 17-24% Al2O3, 0.4-1.2% MgO, 6-8% SO3, and the other properties are in line with the requirements of "Lithium Slag Powder for Cement and Concrete" YB / T 4230-2010.
[0024] The cement is silicate cement with a strength grade of 42.5-52.5.
[0025] The fly ash is selected from one of Class I fly ash and Class II fly ash, or a combination of two or more thereof.
[0026] The sand fineness modulus is 2.3-3.0.
[0027] The crushed stone is a crushed stone with a continuous particle size of 5-25 mm.
[0028] The early strength agent is selected from one or a combination of two or more of triethanolamine, triisopropanolamine, diethanolamine and urea.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The composite water reducer includes a siloxane-modified polycarboxylic acid polymer solution, a POSS-based silane coupling agent, polyethylene glycol, and an alkali activator, wherein the POSS-based silane coupling agent is a sacrificial agent, which can preferentially cover and fill the pore structure on the surface of lithium slag under the action of polyethylene glycol, thereby hindering the adsorption of lithium slag on the siloxane-modified polycarboxylic acid polymer molecules; the siloxane-modified polycarboxylic acid polymer can ensure that it can both adsorb and wrap other gelling particles in concrete and can easily adsorb onto lithium slag particles to play the role of a water reducer; the alkali activator has the effect of compensating for the decreased activity of lithium slag caused by the coverage of the POSS-based silane coupling agent; under the synergistic and balanced action of the above components, the workability of lithium slag concrete can be significantly improved, and the water-reducing effect of the water reducer can be fully exerted. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with specific embodiments, but is not limited to the contents of the specification. Unless otherwise specified, the "parts" described in the embodiments of the present invention are all parts by weight. The reagents used are all commercially available reagents in the art.
[0032] Allyl polyoxyethylene ether with a weight average molecular weight of 2400 and 3000 was purchased from Jinjinle Chemical Co., Ltd.
[0033] The median particle size of lithium slag is 16.5 μm, and the specific surface area is 714.4 m 2 / kg, of which the mass percentage is 8.8% CaO, 61% SiO2, 20% Al2O3, 0.8% MgO, 6% SO3, and the other properties are in line with the requirements of "Lithium slag powder used in cement and concrete" YB / T 4230-2010, purchased from Sichuan Green Ruisang Recycling Resources Utilization Co., Ltd.
[0034] Aminopropylheptyl-cage polysilsesquioxane (CAS No. 444315-15-5) was purchased from Henan Weitixi Chemical Technology Co., Ltd.
[0035] The quartz sand fineness modulus is 2.3 and was purchased from Fengyang Jihui Quartz Sand Co., Ltd.
[0036] 5-25mm continuous particle size graded gravel was purchased from Huzhou Xinkaiyuan Gravel Co., Ltd.
[0037] Polyethylene glycol with number average molecular weight of 600 and 1000 was purchased from Jiangsu Haian Petrochemical Plant.
[0038] Example 1
[0039] 1) Under nitrogen atmosphere, 1 mol (3-acryloxypropyl) trimethoxysilane and 1 mol aminopropylheptyl-cage polysilsesquioxane were added. 874.57900Add to 9.2 mol of chloroform, add 11.1 g of triethylamine, control the temperature at 60°C to react for 3 hours, and after the reaction is completed, remove chloroform and triethylamine by reduced pressure distillation to obtain a POSS-based silane coupling agent.
[0040] 2) Under nitrogen atmosphere, 1 mol of allyl polyoxyethylene ether (weight average molecular weight of 3000), 2 mol of acrylic acid, 3 mol of maleic acid, 0.3 mol of allyl trimethoxysilane, and 1 wt% of thioglycolic acid accounting for the total weight of the monomers are added to 4000 g of water and mixed evenly, heated to 80°C, and a 10 wt% ammonium persulfate solution (solvent is water, ammonium persulfate accounts for 1.5 wt% of the total weight of the monomers) is added dropwise, and the dripping is completed for 1 hour, and then the reaction is carried out at a constant temperature. After the reaction is completed, the pH is adjusted to 7 with a 40 wt% sodium hydroxide solution, and the solid content is adjusted by distillation to remove water, and a siloxane-modified polycarboxylic acid polymer solution with a solid content of 50 wt% is obtained. GPC method for measuring the weight average molecular weight M w It is 68,000.
[0041] 3) 60 kg of siloxane-modified polycarboxylic acid polymer solution, 40 kg of POSS-based silane coupling agent, 5 kg of polyethylene glycol with a number average molecular weight of 600, and 25 kg of sodium hydroxide are mixed evenly to obtain a composite water reducing agent for lithium slag concrete.
[0042] 4) Mix 1 kg of the above composite water reducer and 10.5 kg of water (binder / water ratio is 1:0.35) evenly, add 8 kg of lithium slag and mix evenly, add 20 kg of cement, 2 kg of Grade I fly ash, 0.2 kg of triethanolamine, 65 kg of quartz sand, and 85 kg of continuously graded crushed stone and mix evenly to obtain lithium slag concrete.
[0043] Example 2
[0044] The rest is the same as Example 1, except that in step 3), the amount of siloxane-modified polycarboxylic acid polymer solution used is 40 kg.
[0045] Example 3
[0046] The rest is the same as Example 1, except that, in step 3), the amount of POSS-based silane coupling agent is 25 kg.
[0047] Example 4
[0048] The rest is the same as Example 1, except that in step 3), the amount of polyethylene glycol with a number average molecular weight of 600 is 3 kg.
[0049] Example 5
[0050] The rest is the same as Example 1, except that in step 3), the amount of sodium hydroxide used is 20 kg.
[0051] Example 6
[0052] The rest is the same as Example 1, except that in step 2), the amount of allyltrimethoxysilane used is 0.1 mol.
[0053] M w 65,000
[0054] Example 7
[0055] The rest is the same as Example 1, except that in step 3), the polyethylene glycol with a number average molecular weight of 1000 is used in place of the polyethylene glycol with a number average molecular weight of 600.
[0056] Example 8
[0057] The rest is the same as Example 1, except that in step 4), the amount of the composite water reducing agent is 800 g.
[0058] Example 9
[0059] 1) Under nitrogen atmosphere, 1 mol (3-acryloxypropyl) trimethoxysilane and 1 mol aminopropylheptyl-cage polysilsesquioxane were added to 9.2 mol chloroform, and 11.1 g triethylamine was added. The temperature was controlled at 60° C. to react for 3 h. After the reaction was completed, chloroform and triethylamine were removed by reduced pressure distillation to obtain a POSS-based silane coupling agent.
[0060] 2) Under nitrogen atmosphere, 1 mol of allyl polyoxyethylene ether (weight average molecular weight is 2400), 3 mol of acrylic acid, 2 mol of maleic acid, 0.3 mol of allyl trimethoxysilane, and 1 wt% of thioglycolic acid accounting for the total weight of the monomers are added to 4000 g of water and mixed evenly, the temperature is raised to 80° C., and a 10 wt% ammonium persulfate solution (the solvent is water, and the ammonium persulfate accounts for 1.5 wt% of the total weight of the monomers) is added dropwise for 1 hour, and then the reaction is carried out at a constant temperature. After the reaction is completed, the pH is adjusted to 7 with a 40 wt% sodium hydroxide solution, and the solid content is adjusted by distilling water to obtain a siloxane-modified polycarboxylic acid polymer solution with a solid content of 50 wt%. w It is 71,000.
[0061] 3) 60 kg of siloxane-modified polycarboxylic acid polymer solution, 40 kg of POSS-based silane coupling agent, 5 kg of polyethylene glycol with a number average molecular weight of 600, and 25 kg of sodium hydroxide are mixed evenly to obtain a composite water reducing agent for lithium slag concrete.
[0062] 4) Mix the above 1 kg composite water reducer and 11.2 kg water (binder / water ratio is 1:0.35) evenly, add 5 kg lithium slag and mix evenly, add 25 kg cement, 2 kg Grade I fly ash, 0.2 kg triethanolamine, 80 kg quartz sand, and 100 kg continuously graded crushed stone and mix evenly to obtain lithium slag concrete.
[0063] Comparative Example 1
[0064] Compared with Example 1, the difference is that step 1) is cancelled, and in step 3), the POSS-based silane coupling agent is replaced by an equal mass of aminopropylheptyl-cage polysilsesquioxane.
[0065] Comparative Example 2
[0066] The rest is the same as Example 1, except that in step 3), polyethylene glycol with a number average molecular weight of 600 is not added.
[0067] Comparative Example 3
[0068] The rest is the same as Example 1, except that in step 3), the amount of sodium hydroxide is changed to 15 kg.
[0069] Comparative Example 4
[0070] The rest is the same as in Example 1, except that in step 3), an equal mass of Subot is used. -10 series polycarboxylic acid high-efficiency water reducer replaces siloxane-modified polycarboxylic acid polymer solution.
[0071] The lithium slag concrete prepared in the above examples and comparative examples was subjected to the following performance tests:
[0072] Strength test: refer to GB / T 50081-2002 standard for test methods of mechanical properties of ordinary concrete, standard curing, test 7d compressive strength and 28d compressive strength.
[0073] Chloride ion penetration resistance: refer to the rapid chloride ion migration coefficient method (RCM method) in GB / T 50082-2009 "Standard for test methods of long-term and durability performance of ordinary concrete", and the size of the chloride ion migration coefficient DRCM shall prevail. (The smaller the better)
[0074] Slump / expansion: Tested in accordance with GB / T 50080-2016 Standard test method for performance of ordinary concrete mixtures.
[0075] Table 1 Performance test results
[0076]
[0077]
[0078] It can be seen from the embodiments and comparative examples in Table 1 that with the change of the components of the composite water-reducing agent for lithium slag concrete, the workability of the concrete fluctuates significantly. Under the synergistic effect of the components of the composite water-reducing agent, the workability of the concrete prepared by the present invention is significantly improved, and the role of the water-reducing agent in improving the working performance of the concrete is fully played.
[0079] As can be seen from Table 1 Example 1, Example 5, Comparative Examples 3, the consumption of alkali activator is less conducive to improving concrete workability, it is inferred that the alkali activator has the effect of destroying local POSS-based silane coupling agent covering / filling layer, infiltration, stimulating, the less consumption is the less destruction of the POSS-based silane coupling agent covering / filling on the lithium slag, the poorer the water absorption of lithium slag, and the better the concrete workability; but the less consumption of alkali activator can cause hydration reaction slow, even incomplete, causing concrete poor interfacial bonding, slow strength development, low strength.
[0080] From the test results of the chloride ion penetration resistance in Table 1, it can be seen that under the synergistic effect of the components of the composite water reducer for lithium slag concrete of the present invention, the microstructure of the concrete is improved, the density is increased, and the penetration capacity of chloride ions is reduced.
[0081] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.
Claims
1. A composite water reducing agent for lithium slag concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of siloxane-modified polycarboxylic acid polymer solution, 25-40 parts of POSS-based silane coupling agent, 3-5 parts of polyethylene glycol and 20-25 parts of base activator, wherein the POSS-based silane coupling agent is prepared by Michael addition reaction of acryloxysilane and aminopropylheptyl-cage polysilsesquioxane in a molar ratio of 1:1-1.03; the siloxane-modified polycarboxylic acid polymer solution is prepared by polymerizing monomers of monoalkenyl polyether monomer, acrylic monomer, monoalkenyl dibasic acid and unsaturated siloxane in a solution in a molar ratio of 1:2-3:2-3:0.1-0.3, and the solid content of the polycarboxylic acid polymer solution is 40-50wt%.
2. The composite water reducing agent for lithium slag concrete according to claim 1, characterized in that: The acryloxysilane is selected from one or a combination of two or more of (3-acryloxypropyl)trimethoxysilane, 3-acryloxypropylmethyldimethoxysilane, (methacryloxymethyl)triethoxysilane, (methacryloxymethyl)methyldiethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, methacryloxypropylmethyldiethoxysilane, acryloxypropyltrimethoxysilane, methacryloxymethyltrimethoxysilane, 3-(methacryloxy)propyltrimethoxysilane, 3-trimethoxysilanepropyl acrylate, and 3-(triethoxysilyl)propyl methacrylate.
3. The composite water reducing agent for lithium slag concrete according to claim 1, characterized in that: The POSS-based silane coupling agent is prepared by a method comprising the steps of: Under an inert atmosphere, acryloxysilane and aminopropylheptyl-cage polysilsesquioxane are added to an organic solvent, a catalyst is added, and the temperature is controlled to react. After the reaction is completed, reduced pressure distillation is performed to obtain a POSS-based silane coupling agent.
4. The composite water reducing agent for lithium slag concrete according to claim 1, characterized in that: The monoalkenyl polyether monomer has a weight average molecular weight of 2400-3000 and is selected from one or a combination of allyl polyoxyethylene ether and allyl polyoxypropylene ether; the unsaturated acid monomer is selected from one or a combination of acrylic acid and methacrylic acid; the monoalkenyl dibasic acid is selected from one or a combination of itaconic acid, maleic acid, fumaric acid, and citraconic acid; the unsaturated siloxane is selected from one or a combination of two or more of allyl trimethoxy silane, allyl triethoxy silane, 3-butene triethoxy silane, vinyl trimethyl silane, vinyl triethoxy silane, vinyl dimethoxy silane, and vinyl methyl dimethyloxy silane.
5. The composite water reducing agent for lithium slag concrete according to claim 1, characterized in that: The siloxane-modified polycarboxylic acid polymer solution is prepared by a method comprising the following steps: Under an inert atmosphere, monoolefin polyether monomer, acrylic monomer, monoolefin dibasic acid, unsaturated siloxane and molecular weight regulator are added to water and mixed evenly, the temperature is increased, an initiator solution is added dropwise, and then the reaction is carried out at a constant temperature. After the reaction is completed, the pH and solid content are adjusted to obtain a siloxane-modified polycarboxylic acid polymer solution.
6. The composite water reducing agent for lithium slag concrete according to claim 1, characterized in that: The number average molecular weight of the polyethylene glycol is 600-1000; the activator is selected from one or a combination of two or more of sodium hydroxide, sodium sulfate, gypsum, sodium carbonate and sodium silicate.
7. The method for preparing the composite water reducing agent for lithium slag concrete according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: taking a siloxane-modified polycarboxylic acid polymer solution, a POSS-based silane coupling agent, polyethylene glycol and an alkali activator and mixing them evenly to obtain a composite water reducing agent for lithium slag concrete.
8. A lithium slag concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 200-250 parts of cement, 50-80 parts of lithium slag, 20-40 parts of fly ash, 1-2 parts of early strength agent, 650-800 parts of sand, 850-1000 parts of crushed stone, and 8-10 parts of the composite water reducing agent according to any one of claims 1-6 or 7.
9. The lithium slag concrete according to claim 8, characterized in that: The lithium slag has a median particle size of 15-20 μm and a specific surface area of 500-800 m 2 / kg, of which the CaO content is 5-9%, the SiO2 content is 56-64%, the Al2O3 content is 17-24%, the MgO content is 0.4-1.2%, and the SO3 content is 6-8% by mass percentage.
10. The method for preparing lithium slag concrete according to claim 8, characterized in that: The steps include: Mix the composite water reducing agent and water evenly, add lithium slag and mix evenly, add cement, fly ash, early strength agent, sand and crushed stone and mix evenly to obtain lithium slag concrete.
Citation Information
Patent Citations
A low-autogenous shrinkage high-strength concrete prepared using waste slurry from a concrete mixing plant
CN106316248B
Polyhedron oligomerization sesquialter siloxane-based segmented copolymer and preparation method thereof
CN102206315A
Mud-resistant and salt-resistant polycarboxylate superplasticizer and preparation method thereof
CN103803846A
Silane coupling agent modified polycarboxylate superplasticizer and preparation method thereof
CN105754045A
Polycarboxylate superplasticizer and preparation method thereof
CN112094385A
Cited By
LC3 cement concrete and preparation method thereof
CN120590127A
Comprehensive recovery method of lithium slag
CN120714773A